Cord blood nucleated red blood cell count as a predictor of long term sequelae in cases of perinatal asphyxia: a one-year follow-up study - Kumar, Ashok; Singh, Rupa Dalmia; Suryavanshi, Shashank; Mohan, Kriti (International Journal of Contemporary Pediatrics, 2018)
Background: Nucleated red blood cells (NRBCs) can be easily found in cord blood and its >20/100 WBCs has been distinguished as a marker of perinatal asphyxia at birth. Authors conducted this study to find out if there exists a relation between NRBCs at birth and its effects on long term neurological outcome in patients of perinatal asphyxia. Methods: This was a prospective longitudinal study conducted in the Department of Pediatrics in collaboration with Department of Obstetrics and Gynaecology, G.S.V.M. Medical College, Kanpur from December 2014 to September 2016. Results: On assessing the long term neurodevelopmental outcome in newborns with HIE at birth, Authors found that cord blood NRBCs had no direct influence on the final neurodevelopmental outcome at 1 year of life as did HIE staging. Conclusions: Authors propose that cord blood NRBC counts of > 20/100 WBCs is a good predictor of asphyxia at birth but is definitely not an indicator of forth coming developmental delay.